The Relationship among Website Quality, Consumer Satisfaction, and Loyalty in Vietnamese Banking Sector - Le, Van Huy (University of Economics Ho Chi Minh City, 2023)
Recently, together with the development of information technology, banks have found and put into use more and more channels to deal with their customers, and one of them is the provision of websites to satisfy customers’ need. That is the reason why customer satisfaction in e-banking services is an important challenge to all banks. This study aims to identify the effects of website quality on customer satisfaction, which in turn affects their loyalty toward the banks. For this purpose website quality dimensions, including information quality, navigation, response time, visual appeal, interactivity, security, and innovativeness, are tested by applying regression to the analyses. Additionally, all the data for this research, collected from banking customers through the questionnaires, allow such dimensions as information quality, interactivity, security, and innovativeness to be explored as having contributed significantly to customer satisfaction, which leads to their loyalty to the banks.